2010
DOI: 10.1007/s10620-010-1260-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arthritis in the Course of Inflammatory Bowel Diseases

Abstract: IBDPA is a frequent extra-intestinal complication of IBD. Those of female gender and the presence of Crohn's disease, erythema nodosum and pyoderma gangrenosum have a higher risk to develop IBDPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 15 publications
0
18
0
4
Order By: Relevance
“…and it predominantly affects the joints of the lower limbs . Women show more frequently a peripheral joint involvement, whereas men tend to have an axial involvement [14,15].In our case the patient had findings suggestive of both axial and appendicular skeleton involvement in association with gastrointestinal symptoms.The diagnosis of Enteropathic arthritis was made according to European Spondyloarthropathy Study Group (ESSG) criteria and confirmed with X ray imaging of sacroiliac joints, Immunological profile and IBD on the basis of biopsy.…”
Section: A Case Report Of Juvenile Male With Inflammatory Bowel Diseamentioning
confidence: 43%
“…and it predominantly affects the joints of the lower limbs . Women show more frequently a peripheral joint involvement, whereas men tend to have an axial involvement [14,15].In our case the patient had findings suggestive of both axial and appendicular skeleton involvement in association with gastrointestinal symptoms.The diagnosis of Enteropathic arthritis was made according to European Spondyloarthropathy Study Group (ESSG) criteria and confirmed with X ray imaging of sacroiliac joints, Immunological profile and IBD on the basis of biopsy.…”
Section: A Case Report Of Juvenile Male With Inflammatory Bowel Diseamentioning
confidence: 43%
“…The EIM for patients with UC and CD were being underweight, and having oral ulcers and arthritis. Diarrhea, abdominal pain, being underweight, oral ulcers and arthritis are symptoms of IBD (23)(24)(25). Patients with CD presented a higher proportion of immunoglobulin G, C-reactive protein and erythrocyte sedimentation rate compared with patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…Так, по данным I. Yü ksel и соавт. [31], из 66 больных ВЗК с артритом у 8 (12,1%) внача-ле было зафиксировано развитие суставного синдрома, а впоследствии -кишечной симптоматики. Длительность изолированного поражения опорно-двигательной системы при этом составляла несколько месяцев.…”
unclassified
“…Длительность изолированного поражения опорно-двигательной системы при этом составляла несколько месяцев. Очевидно, что именно у пациентов с дебютом внекишечных проявлений до развития развернутой клинической картины ВЗК возни-кают наибольшие диагностические сложности [31][32][33].…”
unclassified
See 1 more Smart Citation